In vitro performance of one- and two-piece zirconia implant systems for anterior application. (October 2016) - Kammermeier, Armin; Rosentritt, Martin; Behr, Michael; Schneider-Feyrer, Sibylle; Preis, Verena
Abstract: Objectives: To investigate the long-term in vitro performance and fracture resistance of one-piece and bonded two-piece zirconia implant systems for anterior application. Methods: Two groups of bonded two-piece zirconia (ZZB), four groups of one-piece zirconia (Z), and two groups of two-piece titanium (TTS, reference) implant systems were restored with identical monolithic zirconia crowns (n = 10/group). Eight specimens per group were mounted at an angle of 135° in the chewing simulator and subjected to thermal cycling (TC:18, 000 cycles; 5°/55°) and mechanical loading (ML:3.6 × 10 6 cycles; 100N) simulating an anterior situation. Fracture resistance and maximum bending stress were determined for specimens that survived aging and for two references per group after 24 h water storage. SEM pictures were used for failure analysis. Data were statistically analysed (one-way-ANOVA, post-hoc Bonferroni, Kaplan-Meier-Log-Rank, α = 0.05). Results: A one-piece zirconia and a two-piece titanium implant system survived TCML without failures. Both bonded two-piece zirconia implant systems and a one-piece zirconia implant system totally failed (fractures of abutment or implant). Failure numbers of the other systems varied between 1× (1 group) and 5× (2 groups). Significantly different survival rates were found (Log-Rank-test: p = 0.000). Maximum fracture forces/bending stresses varied significantly (ANOVA: p = 0.000) between 188.00 ± 44.80 N/381.02 ± 80.15 N/mm 2 and 508.67 ± 107.00 N/751.45 ± 36.73 N/mm 2 . Mean fracture values after 24 h water storage and TCML were not significantly different. Conclusion: Zirconia implant systems partly showed material defects or connection insufficiencies. Bonded two-piece systems had higher failure rates and lower fracture resistance than one-piece implants. Clinical significance: Individual zirconia implant systems may be applied in anterior regions with limitations.